Customary International Law on the Use of Force - Czapliński, Władysław (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
It is notorious that there are two main positions of international lawyers as to the lawfulness of the use of force in international law. According to the dominant view, the ban on the use of force under the UN Charter is absolute, and force is allowed exclusively in three situations provided in the UN Charter: upon the authorization of the UN Security Council, in self-defence, and against enemy States on the basis of Art.53 and 107, the latter option being purely hypothetical. Rare opponents invoke a strict interpretation of Art.2(4) of the Charter and emphasize that an armed force cannot be used against sovereignty, territorial integrity, or in any other manner contrary to the goals and principles of the UN. Against the background of this dispute a question can be asked whether, the UN Charter notwithstanding, the use of force is regulated by other international legal norms, in particular customary law.
Keywords: użycie siły; Karta Narodów Zjednoczonych; zwyczajowe prawo międzynarodowe